2016
DOI: 10.1001/jamaneurol.2016.0039
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Diagnostic Accuracy of Glial and Neuronal Blood Biomarkers GFAP and UCH-L1 in a Large Cohort of Trauma Patients With and Without Mild Traumatic Brain Injury

Abstract: acidic protein (GFAP) and ubiquitin C-terminal hydrolase L1 (UCH-L1) have been widely studied and show promise for clinical usefulness in suspected traumatic brain injury (TBI) and concussion. Understanding their diagnostic accuracy over time will help translate them into clinical practice.OBJECTIVES To evaluate the temporal profiles of GFAP and UCH-L1 in a large cohort of trauma patients seen at the emergency department and to assess their diagnostic accuracy over time, both individually and in combination, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
349
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 372 publications
(402 citation statements)
references
References 14 publications
24
349
5
8
Order By: Relevance
“…Indeed, alterations in various circulating indices of brain tissue damage such as glial fibrillary acidic protein (GFAP), s100 calcium-binding protein B (s100B), neuron specific enolase (NSE), αII-spectrin N-terminal fragment (SNTF) (22)(23)(24), and inflammatory genes (25,26) have been observed in the acute and subacute phases after SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, alterations in various circulating indices of brain tissue damage such as glial fibrillary acidic protein (GFAP), s100 calcium-binding protein B (s100B), neuron specific enolase (NSE), αII-spectrin N-terminal fragment (SNTF) (22)(23)(24), and inflammatory genes (25,26) have been observed in the acute and subacute phases after SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that UCH-L1 levels rapidly increase in the plasma after brain injury and rapidly decrease subsequently within 36 hours [38]. In a recent study involving mild and moderate TBI, UCH-L1 levels were highly correlated with the GCS scores and the presence of lesions on brain CT [64].…”
Section: Uch-l1mentioning
confidence: 93%
“…In another prospective study, the UCH-L1 concentration in blood was found to be superior to that of GFAP or s100B in predicting the presence of CT lesions within 6 hours after mild and moderate brain injury [65]. However, a recently published prospective cohort study confirmed that the accuracy of UCH-L1 was lower than that of GFAP in determining the presence of brain damage, presence of lesions on CT, and necessity of neurosurgical intervention [38].…”
Section: Uch-l1mentioning
confidence: 97%
See 2 more Smart Citations